npj Quantum Materials - Liu, Jun-Ming.; Cheong, Sang-Wook.; Kivelson, Steven; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Quantum Materials considers research covering all aspects of quantum materials science. The journal covers a broad range of topics including but not limited to: Superconductivity and superconducting materials, including unconventional superconductors, cuprates, iron-based systems, heavy fermion superconductors, other novel superconductors Correlated electronic physics and materials, including mott insulators, magnetism in correlated electron systems, colossal magnetoresistance, multiferroicity and multiferroics, quantum phase transitions, theory and numerical methods in correlated electron systems Topological quantum physics and materials, including topological insulators and topological superconductors, Dirac semimetals and weyl semimetals, Majorana fermions, magnetic topological insulators, novel topological quantum states, topological heterostructures and devices Other correlated systems, including heavy fermions, non-fermi liquids, quantum critical phenomena, quantum hall effects and fractional quantum hall effects, correlations in artificial quantum structures, Bose-Einstein condensation and superfluidity, ultracold atoms and related systems Quantum phenomena in advanced energy materials, including photovoltaic systems, photocatalysis, batteries and fuel cells, thermoelectrics, other advanced energy generation and storage Condensed matter and materials science issues in advanced quantum technologies, including quantum computations, quantum simulations, quantum communications, and quantum sensing The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by quantum materials experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Physics; Astronomy; Condensed matter; Building materials; Surfaces (Technology).; Thin films; Quantum physics; Physics and Astronomy; Condensed Matter Physics; Structural Materials; Surfaces, Interfaces and Thin Film; Quantum Physics